A performance do candomblé: uma encruzilhada no exterior - Petronilio Correia , Paulo (Revista Vozes dos Vales: Publicações Acadêmicas, 2025)
It is proposed that this article show how culture african Brazilian was received and interpreted abroad. France was undoubtedly the greatest space interpretation of Brazilian Candomblé. The tradition of Roger Bastide and his friend Pierre Verger was the beginning of a map and a drawing of Yoruba culture that came broadening the looks and illuminating pathways to a new tradition. Other scholars such as French Giselle Binon-Cossad, Juana Elbein dos Santos, Rita Laura Segato and other foreigners who faced several crossroads to understand the complex dynamics of the yards in Brazil. Each with his gaze and his photograph, a witness in a unique way the complexity of african-Brazilian culture. These looks were significant for the construction of african performances that made the yard one aesthetic, ritualistic and poetic.